Fatal childhood injuries in Finland, 1971–2010. Issue 3 (23rd June 2012) - Parkkari, Jari; Mattila, Ville; Kivistö, Juho; Niemi, Seppo; Palvanen, Mika; Kannus, Pekka
Abstract : Background: Childhood injuries are a major public health problem worldwide, injuries being the leading cause of death and disability from early childhood through adolescence. Objective: To examine the 40-year nationwide trends in the number and incidence of fatal injuries among children aged 0–14 years in Finland, a country with a white European population of 5.3 million. Methods: Data were obtained from the Official Cause-of-Death Statistics of Finland during 1971–2010. The main categories for unintentional injury deaths were road traffic injury, water traffic injury, falls, drowning and poisoning. For intentional injury deaths, the main categories were suicide and homicide. Results: In 1971, there were 109 fatal injuries involving girls and 207 involving boys, and in 2010, these numbers were 10 and 16. The corresponding incidence rates (per 100 000 children per year) were 20.1 and 2.3 (girls), and 36.7 and 3.5 (boys). The reduction in fatal injuries was mostly due to fewer unintentional injuries. The greatest decline occurred in the number of fatal motor vehicle injuries: from 57 (girls) and 92 (boys) in 1971 to 5 (girls) and 2 (boys) in 2010. Drownings followed a similar pattern. Violence-related deaths also showed a decreasing trend. In 1971, there were 14 intentional deaths in girls and 15 in boys, while in 2010 these numbers were 0 and 3, respectively. Conclusions: This nationwide study confirms a decline in childhood injury deaths over the last four decades, with the greatest declines occurring in the number of fatal motor vehicle injuries, drownings and intentional injuries.